Buffalo Cactus and Other New Stories from the Southwest - Myhren, Brett Garcia; Horton, D. Seth, 1976- (Book collections on Project MUSE., 2018)
"Revealing the Southwest as home to some of the most entertaining writers in twenty-first century fiction, this collection features a wonderfully diverse array of authors, including Alberto Álvaro Ríos, Ron Carlson, Jose Skinner, Tacey M. Atsitty, and Kirstin Valdez Quade."--Amazon.com.